Environmental health risk relationships, responsibility, and sources of information among Vietnamese Americans in coastal Mississippi. (17th August 2020) - Covert, Hannah H.; Sherman, Mya; Le, Daniel; Lichtveld, Maureen Y.
Abstract : Coastal communities along the U.S. Gulf of Mexico have been profoundly shaped by environmental health (EH) threats, reflecting the region's history of natural and technological disasters, as well as ongoing issues of environmental degradation and pollution. The Vietnamese American community in the state of Mississippi is vulnerable to EH threats, but there is limited research on their risk perceptions. Understanding perceptions of risk and responsibility is important to manage EH risks and promote community resilience. This community-based participatory research study characterises Vietnamese American perceptions of EH risks, sources of information, and responsibility in coastal Mississippi. Five focus groups were conducted in 2016 and 2017 in Biloxi, Mississippi with Vietnamese Americans working in the seafood industry (n = 24) and mothers of children under the age of 18 (n = 25). Findings related to participants' concerns with air quality, drinking water quality, and the 2010 Deepwater Horizon oil spill are interpreted using Boholm's relational theory of risk. Unreliable access to healthcare and limited English proficiency constrain participants from acting on their environmental health risk relationships. A community-based organisation in Biloxi that works with Vietnamese Americans plays an important role in addressing risk in this population.